2023
DOI: 10.7554/elife.82537
|View full text |Cite
|
Sign up to set email alerts
|

Creating an atlas of the bone microenvironment during oral inflammatory-related bone disease using single-cell profiling

Abstract: Oral inflammatory diseases such as apical periodontitis are common bacterial infectious diseases that may affect the periapical alveolar bone tissues. A protective process occurs simultaneously with the inflammatory tissue destruction, in which mesenchymal stem cells (MSCs) play a primary role. However, a systematic and precise description of the cellular and molecular composition of the microenvironment of bone affected by inflammation is lacking. In this study, we created a single cell atlas of cell populati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…In addition to OSM, our scRNA-seq data showed that periodontal neutrophils highly expressed IL-1 and TNF, suggesting that neutrophils may act as an important source of osteoclastogenic cytokines in periodontal bone loss. 41,42 Since the marked accumulation of neutrophils was also reported in an apical periodontitis model, 43 the neutrophil-osteogenic cell axis may have a role in bone damage associated with endodontic infection. On the other hand, neutrophils can exert anti-inflammatory and bone-protective functions as evidenced by the fact that the neutrophil depletion delayed bone regeneration in a cranial defect model.…”
Section: Discussionmentioning
confidence: 91%
“…In addition to OSM, our scRNA-seq data showed that periodontal neutrophils highly expressed IL-1 and TNF, suggesting that neutrophils may act as an important source of osteoclastogenic cytokines in periodontal bone loss. 41,42 Since the marked accumulation of neutrophils was also reported in an apical periodontitis model, 43 the neutrophil-osteogenic cell axis may have a role in bone damage associated with endodontic infection. On the other hand, neutrophils can exert anti-inflammatory and bone-protective functions as evidenced by the fact that the neutrophil depletion delayed bone regeneration in a cranial defect model.…”
Section: Discussionmentioning
confidence: 91%
“…Similarly, chronic apical periodontitis is an inflammation-related bone disease resulting from root canal infection, where various immune and non-immune cells interact to balance the inflammatory response and promote tissue restoration [ 28 ]. The osteogenic potential of MSCs increases in the inflammatory state of apical periodontitis [ 27 ]. The periapical lesions analyzed in this study were obtained from teeth that had completed root canal treatment and underwent periapical surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Different from many reports on the use of DPSCs for pulp regeneration, and considering the difficulties in obtaining homologous MSCs for clinical application, we selected PLDSCs with multi-lineage differentiation ability, which enriches perspective for the source and subsequent application of maxillofacial related stem cells. The single-cell sequencing of apical periodontitis identified PLDSCs as four different subclusters: osteolineage, endothelial, inflammatory and neurological MSCs, indicating more advantageous in angiogenic and neural differentiation to serve as seed cells for tissue regeneration [ 27 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The immunosuppression and antiā€osteoclastogenic effect of Treg cells is tightly regulated to maintain bone homeostasis in the presence of inflammation (Huang et al., 2022; Zhu et al., 2020). The human apical papilla and its resident cells from teeth with pulp necrosis and apical periodontitis could survive and retain their stemness in an inflammatory environment, therefore regulating infiltration of cellular elements of adaptive immunity (Chrepa et al., 2017; Fan et al., 2023). We observed that Nlrp3 inflammasome was activated in LPS + ATP treated stem cells from apical papilla (SCAPs), resulting in pyroptosis and release of ILā€1Ī² and ILā€6.…”
Section: Discussionmentioning
confidence: 99%